Playing games - Willard, Eliza; Copyright Paperback Collection (Library of Congress) (New York : HarperEntertainment, 2003)
When Ashley starts up a matchmaking service and gets a mystery applicant, there's no telling what will happen.
"A Parachute Press book."
Keywords: Dating (Social customs) -- Juvenile fiction; Twins -- Juvenile fiction; Dating (Social customs) -- Fiction; Twins -- Fiction; Young adult fiction; Love stories